Personal Data Protection in Telemedicine: Comparison of Indonesian and European Union Law - Jannah, Miftahul; Amboro, F. Yudhi Priyo; Shahrullah, Rina (Journal of Law and Policy Transformation, 2023)
Telemedicine allows patients to receive remote medical consultation, diagnosis, and treatment through a digital platform. However, with the development of telemedicine, personal data protection has become one of the main concerns. This research aims to compare the regulation of personal data protection in telemedicine services in Indonesia and the European Union. The type of research in this scientific article is Normative Juridical Research with a comparative legal approach. The data sources obtained in this paper are primary data and secondary data. The data collection method is a literature study. The data analysis method in this paper uses a qualitative approach. The results show that personal data protection in Indonesia is regulated by Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). While in the European Union, Personal Data Protection is regulated in the General Data Protection Regulation (GDPR) which regulates the collection and use of personal data by organizations. Some similarities in personal data protection in both telemedicine in Indonesia and in the European Union are that the same consent requires telemedicine providers to obtain clear and explicit consent from patients. Both telemedicine providers must not disclose the patient's personal data to third parties without the patient's consent. Telemedicine providers to implement security measures to protect patient personal data. Both Indonesia and the European Union give patients the right to access, correct, delete, and limit the use of their personal data